Already have an account? Get multiple benefits of using own account!
Login in your account..!
Remember me
Don't have an account? Create your account in less than a minutes,
Forgot password? how can I recover my password now!
Enter right registered email to receive password!
Determine the function f ( x ) .
f ′ ( x )= 4x3 - 9 + 2 sin x + 7ex , f (0) = 15
Solution
The first step is to integrate to fine out the most general possible
f ( x ) = ∫ 4x3 - 9 + 2 sin x + 7ex
= x4 - 9 x - 2 cos x + 7ex + c
Now we contain a value of the function therefore let's plug in x = 0 and determine the value of the constant of integration c.
15 = f (0) = 04 - 9 (0) - 2 cos (0) + 7e0 + c
= -2 + 7 + c
= 5 +c
Thus, from this it looks like c = 10 . it means that the function is,
f ( x ) = x4 - 9x - 2 cos x + 7ex + 10
1/2+8/9
Write down the first few terms of each of the subsequent sequences. 1. {n+1 / n 2 } ∞ n=1 2. {(-1)n+1 / 2n} ∞ n=0 3. {bn} ∞ n=1, where bn = nth digit of ? So
Prove that A tree with n vertices has (n - 1) edges. Ans: From the definition of a tree a root comprise indegree zero and all other nodes comprise indegree one. There should
Leslie ordered a slice of pizza for $1.95, a salad for $2.25, and a soda for $1.05. What was the total cost of her order? The cost of every item must be added together; $1.95 +
Without solving, find out the Wronskian of two solutions to the subsequent differential equation. t 4 y'' - 2t 3 y' - t 8 y = 0 Solution : First thing that we want to d
Q. Find Common Denominators? What does it mean? Say you have two fractions, like 1/3 and 8/21 And they have different denominators (3 and 21). Sometimes, you'd prefer
By the method of completion of squares show that the equation 4x 2 +3x +5 = 0 has no real roots. Ans: 4 x 2 +3 x +5=0 ⇒ x 2 + 3/4 x + 5 = 0 ⇒ x 2 + 3/4 x +
Prove the subsequent Boolean expression: (x∨y) ∧ (x∨~y) ∧ (~x∨z) = x∧z Ans: In the following expression, LHS is equal to: (x∨y)∧(x∨ ~y)∧(~x ∨ z) = [x∧(x∨ ~y)] ∨ [y∧(x∨
give examples and solutions on my topic
Recently I had an insight regarding the difference between squares of sequential whole numbers and the sum of those two whole numbers. I quickly realized the following: x + (x+1)
Get guaranteed satisfaction & time on delivery in every assignment order you paid with us! We ensure premium quality solution document along with free turntin report!
whatsapp: +1-415-670-9521
Phone: +1-415-670-9521
Email: [email protected]
All rights reserved! Copyrights ©2019-2020 ExpertsMind IT Educational Pvt Ltd